Demokracja związkowa lat 1980-1981 w pamięci i ocenie członków NSZZ „Solidarność” Regionu Bydgoskiego (Kronika Bydgoska, 2018)
The author used the word “outbreak,” since the origins of the “Solidarity” are remembered in this way by its members, who were surprised by it. In the majority of cases they were not prepared to operate in democratic trade union structures. They also had no models to follow, thus guided by intuition and good will they were self-taught in the “Solidarity school of democracy.” They learned mainly by trial and error. The study on communicative, personal memory of students of this “school” encompassed 110 active members of NSZZ “Solidarity” of the Bydgoszcz Region from 1980-1981. Empirical data was collected primarily in three ways: survey (questionnaire), interviews and analysis of documents. The author used a parametric method - catalogued questionnaire-based interview. The study confirmed the rift between the idealistic vision of democracy and its practical implementation. The difference between idea and practice was influenced by lack of experience, human weaknesses and intensive diversion activity of the Security Service.